1974
DOI: 10.3171/jns.1974.40.6.0747
|View full text |Cite
|
Sign up to set email alerts
|

The topography and variability of the primary visual cortex in man

Abstract: ✓ The topographical anatomy of the primary visual cortex in man was studied by macroscopic identification and measurement of the line of Gennari on coronal sections from 52 hemispheres collected at autopsy. Computer analysis of these data provided detailed, quantitative information concerning the amount, variability, and distribution of the striate area on the surface of the occipital lobe, and within the calcarine fissure and other sulci. This information is particularly applicable to the development of a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
170
1
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(201 citation statements)
references
References 22 publications
25
170
1
4
Order By: Relevance
“…This is not surprising since various studies have described variations in functional and anatomical patterns in striate and extrastriate cortex (Aine et al, 1996;Amunts et al, 2000;Dumoulin et al, 2000;Gilissen et al, 1995;Gilissen and Zilles, 1996;Hasnain et al, 1998;Rademacher et al,1993;Roland et al,1997;Steinmetz et al, 1990;Steinmetz and Seitz, 1991;Stensaas et al, 1974;Watson et al, 1993) The variability found here can mainly be attributed to variations in gross anatomy and variations in the relationship between gross anatomy and functional areas, rather than methodological differences.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This is not surprising since various studies have described variations in functional and anatomical patterns in striate and extrastriate cortex (Aine et al, 1996;Amunts et al, 2000;Dumoulin et al, 2000;Gilissen et al, 1995;Gilissen and Zilles, 1996;Hasnain et al, 1998;Rademacher et al,1993;Roland et al,1997;Steinmetz et al, 1990;Steinmetz and Seitz, 1991;Stensaas et al, 1974;Watson et al, 1993) The variability found here can mainly be attributed to variations in gross anatomy and variations in the relationship between gross anatomy and functional areas, rather than methodological differences.…”
Section: Discussionsupporting
confidence: 64%
“…6 provides a validation of the method described here. In the calcarine sulcus a large region of negative field sign (mirror image) is present, around which regions opposite field sign can be distinguished corresponding to the known layout of areas V1 and V2 (Amunts et al, 2000;Clarke and Miklossy, 1990;Gilissen et al, 1995;Gilissen and Zilles, 1996;Holmes, 1945;Horton and Hoyt, 1991;Rademacher et al, 1993;Stensaas et al, 1974;Wong Fig. 6.…”
Section: Volumetric Visual Field Sign Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…anatomy and folding patterns are highly variable among individuals (Stensaas et al, 1974), and we do not have access to the individual MRIs that could confirm it.…”
Section: P2 Componentmentioning
confidence: 99%
“…In humans, the primary areas, motor (M1), somatosensory (S1), and visual (V1), vary Ϸ2-fold in size in a smooth continuum (1)(2)(3)(4)(5). In mice, the sizes of V1 and the S1 barrelfield are very consistent within inbred strains of mice, but their mean sizes can differ between some inbred strains of mice (6).…”
mentioning
confidence: 99%